Design of orbital maneuvers with aeroassisted cubesatellites - Clark, Stephanie Joy (ProQuest Dissertations & Theses, 2012)
Recent advances within the field of cube satellite technology has allowed for the possible development of a maneuver that utilizes a satellite's Low Earth Orbit (LEO) and increased atmospheric density to effectively use lift and drag to implement a noncoplanar orbital maneuver. Noncoplanar maneuvers typically require large quantities of propellant due to the large Δ-υ that is required. However, similar maneuvers using perturbing forces require little or no propellant to create the Δ-υ required. This research reported here studied on the effects of lift on orbital changes, those of noncoplanar types in particular, for small satellites without orbital maneuvering thrusters. In order to test the effect of perturbing forces, a Runge-Kutta-based computer model was developed using MATLAB. Fundamental differential equations of satellite motion were used to propagate the time, position, and velocity for each experimental orbit. This model requires the input of initial position and velocity (defined by the Earth-Centered Cartesian Coordinate system), constants, and the number of intervals. In addition, the model used an upper atmosphere model created from the Atmospheric Standard of 1976 to approximate density at altitudes to 1000 kilometers, covering well beyond the interested altitude on the order of 100's of kilometers. Utilizing the orbital model, a lift comparison was completed between a constant angle of attack and scheduled change of the angle of attack; both comparisons were done with varying accommodation coefficients. In addition, a lift comparison was also completed based on scaling laws to analyze any differing effects caused by increase mass and surface area.